2023
DOI: 10.3390/ma16062375
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Ozone Therapy in Reducing Periodontal Disease

Abstract: The aim of this study is to highlight the properties of ozone as an aid to non-surgical therapy compared to non-surgical therapy alone. This study included thirty Caucasian patients (eighteen women and twelve men) aged between 35 and 65, recruited at the Oral Hygiene and Prevention Center of the Dental Clinic of the Vita-Salute San Raffaele University, at the San Raffaele hospital in Milan. The periodontal probing was recorded with a PC-PUNC 15 manual probe (Hu Friedy) at time 0; the scaling and root planing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…When ozone is applied to the oral cavity, it can exert antimicrobial effects by disrupting the cell walls of microorganisms and interfering with their metabolic processes. This makes ozone an attractive option for treating infections caused by periodontal pathogens and Candida species, which are known to play significant roles in periodontal disease and oral thrush, respectively [ 92 , 93 , 94 , 95 ]. Several research papers have reported positive outcomes when using ozone therapy in conjunction with conventional dental treatments.…”
Section: The Uses Of Ozone In Dentistrymentioning
confidence: 99%
“…When ozone is applied to the oral cavity, it can exert antimicrobial effects by disrupting the cell walls of microorganisms and interfering with their metabolic processes. This makes ozone an attractive option for treating infections caused by periodontal pathogens and Candida species, which are known to play significant roles in periodontal disease and oral thrush, respectively [ 92 , 93 , 94 , 95 ]. Several research papers have reported positive outcomes when using ozone therapy in conjunction with conventional dental treatments.…”
Section: The Uses Of Ozone In Dentistrymentioning
confidence: 99%
“…Ozone, composed of three oxygen atoms, rapidly breaks down into oxygen, with one oxygen atom serving as a potent oxidant that can eliminate microorganisms and activate antioxidant enzymes ( 6 ). Studies have demonstrated the application of ozone therapy in various conditions, including periodontitis, pain management, tumors, and diabetic wounds ( 7 10 ). As an adjunct therapy for DFUs, the effectiveness of ozone therapy varies.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous other approaches have been described in the literature to increase the effectiveness of non-surgical therapy, such as ozone, the addition of erythritolchlorhexidine powder, probiotics, laser therapy, hyaluronic acid, omega-3, omega-6, and drugs such as antibiotics or other medications [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
mentioning
confidence: 99%